Genetic and molecular regulation of chilling requirements in pear: breeding for climate change resilience - Gabay, Gilad; Flaishman, Moshe A. (Frontiers in Plant Science, 2024)
Pear (Pyrus spp.) is a deciduous fruit tree that requires exposure to sufficient chilling hours during the winter to establish dormancy, followed by favorable heat conditions during the spring for normal vegetative and floral budbreak. In contrast to most temperate woody species, apples, and pears of the Rosaceae family are insensitive to photoperiod, and low temperature is the major factor that induces growth cessation and dormancy. Most European pear (Pyrus Communis L.) cultivars need to be grown in regions with high chilling units (CUs) accumulation to ensure early vegetative budbreak. Adequate vegetative budbreak time will ensure suitable metabolite accumulation, such as sugars, to support fruit set and vegetative development, providing the necessary metabolites for optimal fruit set and development. Many regions that were suitable for pear production suffer from a reduction in CUs' accumulation. According to climate prediction models, many temperate regions currently suitable for pear cultivation will experience a similar accumulation of CUs as observed in Mediterranean regions. Consequently, the Mediterranean region can serve as a suitable location for conducting pear breeding trials aimed at developing cultivars that will thrive in temperate regions in the decades to come. Due to recent climatic changes, bud dormancy attracts more attention, and several studies have been carried out aiming to discover the genetic and physiological factors associated with dormancy in deciduous fruit trees, including pears, along with their related biosynthetic pathways. In this review, the current knowledge of the genetic mechanisms associated with bud dormancy in European pear and other Pyrus species is summarized, along with metabolites and physiological factors affecting dormancy establishment and release and chilling requirements determination. The genetic and physiological insights gained into the factors regulating pear dormancy phase transition and determining chilling